PENATALAKSANAAN TERAPI RADIASI EKSTERNA PADA KASUS KANKER VULVA DENGAN TEKNIK IMRT DAN ALAT FIKSASI PENGGANJAL LUTUT KHUSUS - Septi Hidhayani; Agus Budiman; Mayarani; Susy Suswaty (Perhimpunan Radiografer Indonesia (PARI), 2019)
Introduction: Invasive vulvar cancer is very small. Usually occurs in women, but at the same time. An average of 90% - 92% of vulvar cancer patients are squamous cell carcinomas. Treatment of vulvar cancer is surgery, radiotherapy, chemotherapy or even combination according to the stages and references of each patient. In Dr. Cipto Mangunkusumo, Radiotherapy was selected to be one of the treatment options for stage III-IV vulvar cancer because it can provide maximum value on target and minimum on healthy tissue by using IMRT technique and frog leg position with special sterofoam feed fixation tool. Objective: Describe the procedure for managing external radiation therapy in cases of vulvar cancer with IMRT technique and a special fungicide feeding device at the Radiotherapy Department Dr. Rsupn. Cipto Mangunkusumo. Method: The type of descriptive skin research by observing directly and recording the required data and approach with case study, discussion and question and answer with radiotherapist, radiation oncologist and patient at the Department of Radiotherapy RSUPN. Cipto Mangunkusumo in march 2018. The sample used is 1 primary data sample of patients with vulvar carcinoma squamosa cell IVA. Results: Patients with IV carcinoma of squamous cell carcinoma A treatment plan with qualitative RT objective, using 10 MV energy, radiation plan 25 x @ 2 Gy. With IMRT technique and special fixture fixture tool from sterofoam to position the patient to form the frog spring. Conclusion: The use of IMRT techniques and semi frog leg positioning is highly appropriate and effective for vulvar cancer. It comes from DVH achievement doses at very maximum targets and on the minimal surrounding organs and patient comfort. The cost value of the IMRT technique is 0.2 cm